Synthesis of Ferric Oxide Urea Formaldehyde Nanocomposite for Adsorptive Removal of Malachite Green Cationic Dye from Aqueous Media (International Journal of Scientific Research in Science and Technology, 2024)
The main objective of current research is to synthesise ferric oxide nanoparticles and prepare their nanocomposite from urea formaldehyde resin. Characterization techniques such as FTIR, XRD, and FESEM-EDX were used to obtain the specifications of the synthesised nanoparticle. Synthesised ferric oxide urea formaldehyde nanocomposite was used for the adsorption of malachite green (MG) dye from wastewater. The adsorption tests were implemented at various parameters. The adsorption capacity could reach 98% within a contact time of 80 min at pH 7 and an initial dye concentration of 50 ppm. It was finally retained that the adsorption rate of malachite green dye by ferric oxide urea formaldehyde nanocomposite follows pseudo second-order kinetics with the adsorption isotherm fitted by the Langmuir isotherm model well. All the above results demonstrated that ferric oxide urea formaldehyde nanocomposite has a significant potential for the removal of malachite green dye from wastewater.